Soft tissue organization of the deep water hexactinellid Schaudinnia arctica Schulze, from the Arctic Seamount Vesterisbanken (Central Greenland Sea). - Mehl, D.; Reitner, J.; Reiswig, H.M. (Berliner geowissenschaftliche Abhandlungen Reihe E (Paläobiologie), 1994)
Histology and ultrastructure of the hexactinellid arctic deep sea sponge Schaudinnia arctica are investigated. Various techniques of fluorescence microscopy proven to be very informative for the study of poriferan soft tissues are applied. These methods for use in sponge research are explained in detail. The histology shows that Schaudinnia arctica on the whole corresponds with earlier models of hexactinellid organization. However, the collagenous mesolamella are surprisingly thick compared with those of other hexactinellids described so far. Spectacular accumulations of granular cells with larger inclusions are observed throughout the entire sponge body. Transitional cell types indicate an ontogenetic succession from archaeocytes to granular cells in Schaudinnia arctica. According to observations in UV-fluorescence microscopy with different staining methods, the large inclusions of these granular cells contain little glycogen, but high ca2+- contents. According to comparisons with similar cells of demosponges, it is suggested that the granular cells may function as storage cells for lectins, which play an important role in the metabolism of sponges.